1985
DOI: 10.1007/bf00684373
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase activity at the synapses of presynaptic boutons with presumedα-motoneurons in chicken ventral horn

Abstract: Acetylcholinesterase (AChE) activity at the synapses of presynaptic boutons on presumed alpha-motoneurons in the chicken ventral horn was studied histochemically at the light- and electron-microscope levels. At the light-microscope level, many dot-like AChE-active sites were observed on the soma and dendrites of presumed alpha-motoneurons. On electron microscopy, reaction products for AChE activity were observed mainly in the synaptic clefts of the four kinds of presynaptic boutons: (1) S type boutons, (2) bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…40 We found by light microscopy double immunolabelling methods that subsurface cisterns co-localize with choline acetyltransferase (ChAT)-labelled boutons on motoneurons at most cranial and spinal levels, 24 which is consistent with electron microscopic observations that C-terminals on motoneurons in the hypoglossal nucleus are cholinergic, based on their immunolabelling for ChAT. 8 In agreement with electron microscopy histochemical results showing high concentrations of acetylcholinesterase (AChE) reaction product at motoneuronal C-terminal subsurface cistern complexes, 10,34 a high degree of co-localization was found between immunofluorescence labelling for subsurface cisterns and AChE. 24 These results, together with our observations that large ChAT-containing boutons on motoneurons correspond to those containing AChE, suggested that most, if not all, C-terminals are cholinergic.…”
supporting
confidence: 83%
“…40 We found by light microscopy double immunolabelling methods that subsurface cisterns co-localize with choline acetyltransferase (ChAT)-labelled boutons on motoneurons at most cranial and spinal levels, 24 which is consistent with electron microscopic observations that C-terminals on motoneurons in the hypoglossal nucleus are cholinergic, based on their immunolabelling for ChAT. 8 In agreement with electron microscopy histochemical results showing high concentrations of acetylcholinesterase (AChE) reaction product at motoneuronal C-terminal subsurface cistern complexes, 10,34 a high degree of co-localization was found between immunofluorescence labelling for subsurface cisterns and AChE. 24 These results, together with our observations that large ChAT-containing boutons on motoneurons correspond to those containing AChE, suggested that most, if not all, C-terminals are cholinergic.…”
supporting
confidence: 83%
“…In histochemical investigations of AChE, enzyme reaction product, although widely distributed, was found predominantly at synaptic clefts formed by C-terminals on motoneurons in hypoglossal, facial, and cervical motor nuclei of rat (Davidoff and Irintchev, 1986). In a study of AChE in chicken ventral horn, enzyme reaction product was also localized to some C-terminals, as well as several other terminal types on motoneurons (Sakamoto et al, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…Our results are consistent with these earlier descriptions and demonstrate somewhat more clearly the presence of ChAT-positive "terminals" on motoneuronal cell bodies, as well as their proximal dendritic segments. Similarly, although AChE has been investigated by histochemical methods in the spinal cord of several species (Butcher et al, 1977;Odutola, 1972;Satoh et al, 1983;Silver and Wolstencroft, 19711, reaction product of this enzyme is not readily visualized by LM in nerve endings associated with motoneurons, but as discussed below has been localized to discrete types of terminals on these neurons by EM (Lewis and Shute, 1966;Davidoff and Irintchev, 1986;Sakamoto et al, 1985). AChE in the CNS has also been examined by immunohistochemical techniques (Andra et al, 1988;Bean et al, 1991;Rakonczay and Brimijoin, 1986), but to our knowledge detailed analyses of AChE-IR elements in spinal cord have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Correlative light-electron microscopic analysis of ChAT-IR confirmed C-boutons are cholinergic (Houser et al, 1983; Connaughton et al, 1986; Li et al, 1995), a suggestion first made decades prior with ultrastructural acetylcholinesterase (AChE) histochemistry (Lewis and Shute, 1966), which alone is not sufficient for cholinergic classification (Fibiger, 1982; Satoh et al, 1983; Sakamoto et al, 1985; Davidoff and Irintchev, 1986; Nagy et al, 1993). In support, VAChT is highly associated with small clear synaptic vesicles in the C-bouton presynaptic terminal (Gilmor et al, 1996) and there is a strong association throughout the brainstem and spinal cord between large ChAT-IR synaptic boutons on α-MNs and SSCs immunolabeled for connexin32 (Nagy et al, 1993).…”
Section: Moments and Milestones: Transmitter Contentmentioning
confidence: 97%